Competition law and the Malaysian financial services market: an analysis of the structure and level of competition in the market - Abdul Rahman, Nasarudin; Mohamad Faudzi, Mohd Hasbullah; Ahamat, Haniff; Abd Ghadas, Zuhairah Ariff (Inderscience Enterprises Ltd., 2016)
The main objective of competition law is to protect the process of competition by preventing anti-competitive behaviour such as abuse of dominant position and anti-competitive mergers. The assessment of market structure and the level of competition in the financial sector are important for the exercise of the competition authority’s power to enforce the national competition law. It helps the competition authority to better understand the nature of the financial services market such as the existence of market power and features that facilitate anti-competitive behaviour. This paper attempts to analyse structure of the market and the level of competition in the Malaysian financial market using two measures, namely concentration ratio (CR) and Herfindahl–Hirschman index (HHI). The study shows that the banking sector can be considered as ‘unconcentrated’. However, based on ownership (foreign or local) the study indicates such sector is ‘moderately’ concentrated. For the insurance sector, general insurance can be considered as ‘unconcentrated’, whereas life insurance is ‘highly concentrated’.